Une réécriture amérindienne du théâtre de Shakespeare : Hamlet-le-Malécite - Françoise Besson (Anglophonia)
A recent Canadian rewriting of Shakespeare’s Hamlet stages characters in a Native Canadian reserve in Quebec. This paper shows how theatrical mixity may be seen as an element of resistance and the mise en abyme of theatre as an instrument of denunciation of the evils of the time. This Canadian play exposes all the evils afflicting the First Nations today and all the damage caused to their territories for the sake of profit. The play, using several languages, also illustrates how language may be an element of resistance through the depiction of the predicament of a particular community inscribed in the eternally repeated history of mankind.